(3JWhQ QCS eGd GdTQcI h eaghe GdQHM aj GdTQcGJ GdJLGQjI (B/s - (3JhfSj, MSjfs ((3GdLRGFQ(B: s (3OGQ GdNdOhfjI(B, s, 2008)
(3ebOeGJ Mhd GdTQcI , GdebUhO HGdTQcI h CgejJgG GdGbJUGOjI h GdGLJeGYjI , GdWHjYI GdbGfhfjI ddTQcI h CfhGYgG h GdbhGYO GdYGeI GdeSGgeI , eaghe GdQHM aj GdTQcGJ GdfLGQjI h GdebUhO Hg , GdBKGQ GdfGJLI Yf hLhO GdCQHGM (B.s
(3eQGLY U(B.156 (3; edGMb U(B.159s
Keywords: (3GdTQcGJs; (3GdeDSSGJ GdJLGQjIs; (3QCS GdeGds